Fish meal Substitution by earthworm meal (Libyodrilus violaceus) in diets for African catfish, (Clarias gariepinus) (African Journal of Fisheries Science, 2014)
A seven-week feeding trial was conducted to examine the possibility of replacing fish meal with earthworm meal in the diets of the African catfish, Clarias gariepinus fry. Fish meal protein was replaced by earthworm meal at 0% (D0); 15% (D15); 25% (D25); 35% (D35); and 50% (D50). The diets were isonitrogenous (54%) and fed thrice daily to triplicate groups of African catfish fry at 5% body weight. Diet had a significant effect on growth performance and feed utilization (p≤0.05). Final weight, weight gain, daily weight gain, and specific growth rate, were highest in fish fed diet D25. A similar pattern of growth was observed for length measurements. Fish fed diets exceeding 25% replacement of fish meal with earthworm meal had depressed growth. Feed conversion ratio was highest in fish fed D35. Mortality was not dependent on diet. It is concluded that fish meal can be substituted with earthworm meal up to 25% in the diet of C. gariepinus fry without adverse effects on growth and nutrient utilization.